Unified approach for the total aynthesis of Bis-THF C-15 acetogenins: a chloroenyne from laurencia majuscula, laurendecumenyne B and laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis-Stuttgart, 2021)
A highly diastereoselective total synthesis of several bis-THF C-15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenyries A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, S(N)2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C-15 acetogenins; carbohydrate building block; relay-cross-metathesis; S(N)2 halogenation; Sharpless asymmetric dihydroxylation-cycloetherification

Unified approach for the total synthesis of Bis-THF C-15 acetogenins: a chloroenyne from laurencia majuscula, laurendecumenyne B and laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis-Stuttgart, 2021)
A highly diastereoselective total synthesis of several bis-THF C-15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenyries A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, S(N)2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C-15 acetogenins; carbohydrate building block; relay-cross-metathesis; S(N)2 halogenation; Sharpless asymmetric dihydroxylation-cycloetherification

Concise approach for the synthesis of the tetracyclic framework of Lycibarbarines A and B - Shet, Manoj N.; Nechooli, Hemanth K.; Ramana, Chepuri V. (Tetrahedron Letters, 2023)
A simple approach for the construction of the tetracyclic spiroketal skeleton of Lycibarbarine A and B has been described. Employing a solvent free condition for epoxide opening with tetrahydroquinoline as a key reaction to couple both the fragments, an oxidation followed by TBAF-mediated silyl deprotection spiroketalization establishes the complete tetracyclic core present in these natural products. (c) 2023 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool approach; D -Glyceraldehyde; Tetracyclic spiroketal; Total synthesis

Total synthesis of (-) and (+)-zingibergingerols A - Shet, Manoj N.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2024)
The first total synthesis of both of the enantiomers of Zingibergingerol A has been accomplished. The distinctive 3,7,9-trioxabicyclo[4.2.1]nonane skeleton is crafted through gold-catalyzed alkynol cycloisomerization. The synthesis comprises sequential C-C bond formations at both ends of epichlorohydrin: first opening the epoxide with eugenol-derived alkyne, followed by subsequent epoxide installation, and again opening with a Grignard reagent. The resulting alkynol with a fixed C5 stereochemistry was subjected to O-allylation, followed by dihydroxylation and alkynol cycloisomerization.

Total synthesis of triplinone F - Shet, Manoj N.; Wabale, Krishna R.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2026)
The first total synthesis of triplinone F, along with its C11 epimer, has been executed to establish, inter alia, the stereochemistry of C11 and its complete absolute configuration. The terminal styrene unit was added by cross-metathesis, whereby 1,3-diol units on either side of the central olefin were taken from malic acid enantiomers and coupled by a Yamaguchi alkyne-epoxide opening protocol. The C11 stereochemistry was manipulated by Noyori asymmetric ynone reduction. The Z-selective reduction of alkynoate and acid-catalyzed lactonization forged the right-hand-side 5,6-dihydro-delta-pyrone unit.